The trend of higher-order multiple gestation in a tertiary hospital in South-South Nigeria - Iwo-Amah, Rose Sitonma; Wekere, Felix Clement C.; Ocheche, Uduak; Awoyesuku, Peter Abiye; Horsefall, Faithwin; Bema, Elizabeth (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Higher-order multiple (HOM) Gestations are pregnancies with three or more fetuses within the uterus at the same time. The advent of assisted reproductive technology (ART) has caused an increase in its occurrence. Prevalence of naturally occurring HOM births is 1-7 per 10,000 deliveries. HOM are associated with adverse obstetric and perinatal outcomes, when compared with singleton births. In Nigeria, ART is gaining ground, after an initial reluctance. The aim of this study was to highlight the adverse obstetric and perinatal outcomes of HOM pregnancies and births in a tertiary hospital. Methods: This was a retrospective study of 38 HOM pregnancies that delivered at the Rivers State University Teaching Hospital (RSUTH) between January 2019- December 2023. Relevant data was extracted from the patient’s hospital records. Data was entered into a pre-designed Proforma. Analysis was done using IBM.SPSS, version 25. Results: A total of 9,538 deliveries took place within the study period. Two hundred and ninety (3.04%) were twin deliveries. Triplet deliveries were 33(0.35%). Quadruplets were a total of 4 (0.04%) and Quintuplets delivery was 1(0.01%). Prevalence of HOM births from this study was 3.7 per 1,000 deliveries. Complications associated with HOM deliveries for the parturient were anaemia (84.2%) and severe pre-eclampsia (42.12%). Perinatal complications were prematurity (92.12%), low birth weight (91.5%) and respiratory distress syndrome (90%). Conclusions: There is an upward trend of HOM pregnancies due to ART, and advanced maternal age at conception. Proper antenatal care to prevent anemia, close monitoring of these pregnancies will help improve maternal and perinatal outcomes from HOM births.